Comparison of Acoustic Emission and Structure Degradation in Compressed Porcelain and Corundum Materials - RANACHOWSKI, Przemysław; REJMUND, Feliks; RANACHOWSKI, Zbigniew; PAWEŁEK, Andrzej; PIĄTKOWSKI, Andrzej (Archives of Acoustics, 2009)
The paper presents the results of acoustic emission (AE), microscopic and ultrasonic measurements of the samples subjected to slowly increasing compressive stress. On the basis of performed measurements, the successive stages of the materials structural degradation have been recognized. The object of research and comparison were the samples made of the electrotechnical materials - aluminous porcelain and corundum ceramics. Both investigated materials have wide technical application. The analysis of obtained mechanoacoustic characteristics pointed out a complicated mechanism of degradation of the materials. Microscopic investigation of samples, which were stressed to different levels of load, enabled to specify the various course of the gradual growth of microcracks and successive crushing out of elements of the structure. These effects appear to be similar to the aging processes occurring in the materials during long periods of exploitation under working load. For the two tested materials there were distinguished three stages of the structure degradation. The preliminary and subcritical ones show low or moderate intensity of AE signals and considerable variety for the particular samples. The critical stage directly precedes destruction of the samples. Its range is relatively narrow and contains AE activity of high energy. The presented results enable to draw up conclusions concerning the resistance of investigated materials to the aging degradation processes development during long-term operation. Comparison of the results of mechanical, acoustic and microscopic studies have revealed that the differences registered for the strength and characteristics are due to inhomogeneities of the materials in the semi-macro as well as in the micro-scale. The effectiveness of dispersive and fibrous reinforcement of aluminous porcelain was described. Strengthening of porcelain by corundum grains and mullite needle-shaped crystals improves mechanical parameters and distinguishes this material from typical aluminosilicate ceramics. The occurrence of groupings of bigger grains in the structure of the corundum material represents most probably the intermediate state, leading to the known effect of the abnormal grain growth (AGG).